Crimean-Congo hemorrhagic fever with severe bradycardia treated with Theophylline - Murat Aydın; Nurten Nur Aydın (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne viral hemorrhagic fever caused by Nairovirus and characterized by fever, myalgia, arthralgia, and hemorrhagic manifestations. Severe bradycardia is a rare complication of the disease. We present a 30-year-old male patient with CCHF who developed severe bradycardia, which was successfully treated with intravenous and oral theophylline. This case highlights the need to recognize cardiac complications in CCHF and highlights the role of pharmacological interventions in improving patient outcomes.